Organic mental disorders in children and adolescents with a history of blood cancer - O. A. Suetina (Русский журнал детской неврологии, 2020)
We performed clinical examination of 60 children and adolescents in remission followed up in Research Institute of Pediatric Oncology and Hematology, N.N. Blokhin National Medical Research Center of Oncology. All patients were found to have complex organic disorders of varying severity, primarily induced by aggressive methods of treatment (such as polychemotherapy, high-dose chemotherapy, and cranial irradiation).